Advanced Passenger Security System for Radio Cabs with Video Transmission and Enhanced System Security with Biometric Module - Sharma, Jyotika; Bhat, Mushafiq Hassan; Ghildiyal, Stuti; Bashir, Danish (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
and radio systems in every field, the use of better communication technology has been the prime focus for all major industries. India has been adopting such systems on a large scale to meet the demands of alarge and diverse population. Radio Cabs have been on a tremendous hike during the past so many years. The industry has crossed a record breaking turn over with all the companies aiming for better and comfortable services. During the past three to five years, Delhi has seen some worst rape and crime scenes involving cabs directly or indirectly. This raises a question mark on the safety and reliability of these services even in the capital city of one of the world’s fastest growing countries. This project is based on increasing the safety and reliability of these services.